Blended Learning in Islam Ulil Albab Course and Its Contribution To Enhance Students’ Piety - Sri Haningsih; Shubhi Mahmashony Harimurti; Anisah Budiwati (Millah: Journal of Religious Studies, 2022)
Conventional face-to-face or offline learning is considered outdated for students in today's digital era. However, online learning, which is considered new and meets nowadays learning, still lacks practice. This research is aimed to provide a solution for combining online and offline teaching; at the same time, to offer an approach to develop students’ piety. The proposed innovation is to apply blended learning. This method emphasizes students’ active roles in their learning. Digital devices used include YouTube, Google Classroom, and Interactive Mentimeter. The methods used in this research were classroom action research and literature studies. The learning model used was flipped Classroom; offline meetings used textbooks, and online lectures used online videos. The main objective is to link blended learning media with the development of piety among the Chemical Analysis department students. The results indicate that collaborative and contextual learning meet students’ needs in developing piety. In conclusion, blended learning also helps students to formulate their contributions to Islamic civilization in the future.